2019
DOI: 10.1063/1.5084961
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of trajectory surface hopping methods: Ultrafast internal conversion in pyrazine

Abstract: Trajectory surface hopping (TSH) methods have been widely used to study photoinduced nonadiabatic processes. In the present study, nonadiabatic dynamics simulations with the widely used Tully's fewest switches surface hopping (FSSH) algorithm and a Landau-Zener-type TSH (LZSH) algorithm have been performed for the internal conversion dynamics of pyrazine. The accuracy of the two TSH algorithms has been critically evaluated by a direct comparison with exact quantum dynamics calculations for a model of pyrazine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(109 citation statements)
references
References 90 publications
5
103
1
Order By: Relevance
“…We employed a recently developed Landau-Zener (LZ) surface-hopping algorithm. [44][45][46][47] This algorithm is a computationally efficient and accurate alternative to the widely used fewest-switches surface-hopping (FSSH) method of Tully. 48 In the LZ-based surface-hopping (LZSH) algorithm, the transition probability between electronic states is determined directly from the topography of the adiabatic potentials in energy-crossing regions, avoiding the computation of rapidly varying derivative couplings near avoided crossings and conical intersections (CIs).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We employed a recently developed Landau-Zener (LZ) surface-hopping algorithm. [44][45][46][47] This algorithm is a computationally efficient and accurate alternative to the widely used fewest-switches surface-hopping (FSSH) method of Tully. 48 In the LZ-based surface-hopping (LZSH) algorithm, the transition probability between electronic states is determined directly from the topography of the adiabatic potentials in energy-crossing regions, avoiding the computation of rapidly varying derivative couplings near avoided crossings and conical intersections (CIs).…”
Section: Methodsmentioning
confidence: 99%
“…The results of simulations with the LZSH method have been compared with those of simulations with the FSSH method and with the results of exact quantum dynamics calculations in several studies of few-state few-mode model systems. [45][46][47] In the present work, we used an implementation of the LZSH method based on MP2 and ADC (2) energies and gradients computed with the TURBOMOLE program package. 47 Similar ab initio on-thefly LZ-based trajectory SH simulations of the photochemical dynamics of molecular systems were recently performed by Zhu and coworkers 49 and Kono and coworkers 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Pyrazine is a molecule with 24 degrees of freedom and complicated dynamics, which is governed by a conical intersection between the S 1 and S 2 electronic states. A considerable amount of theoretical investigations, ranging from fully quantum dynamics simulations 59 to semiclassical direct dynamics, 54 revealed the S 1 and S 2 vibronic coupling dynamics in pyrazine.…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 23 Recently, it has been shown that nonadiabatic dynamics simulations with the Landau–Zener algorithm and the FSSH algorithm produce very similar results. 54 The main difference between both approaches is the way how the hopping probability from state i to state j is computed. In Tully’s approach, this is done as a function of the coefficients of the electronic wavefunction and the nonadiabatic coupling vector.…”
Section: Pysurf: Application Domainmentioning
confidence: 99%
See 1 more Smart Citation